Utility of prediction models in growth hormone therapy in children with idiopathic growth hormone deficiency. (24th May 2012) - Balendran, G; Acerini, CL
Abstract : Aims: Growth prediction models are thought to be helpful in detecting children with Idiopathic Growth Hormone Deficiency (IGHD) with poor response to recombinant human growth hormone (rhGH) therapy. This study aims to determine adequacy of rhGH therapy responses in the first two years of treatment in children with IGHD by comparing with a validated prediction model. Methods: Growth records of IGHD patients started on rhGH therapy between 1999 and 2009 at single tertiary endocrinology centre were analysed in order to calculate pre-treatment, year one and year two height velocities (HVs). HVs were expressed as standard deviation score (SDS). Growth prediction formula determinants (age at onset, birth weight SDS, height SDS, weight SDS, mid-parental height SDS, maximum GH on stimulation test and rhGH dose) were obtained. Observed and predicted HVs were compared using an unpaired t-test. Results: Of 54 patients identified, 18 pre-pubertal children (median (range) age 10 (4-16) years; 13 male) had sufficient data for HV analysis (figure 1 ). In year one, 3 of the 18 patients received an rhGH dose below recommended national prescribing guidelines (0.7–1.0 mg/m 2 /day), increasing to 5 patients in year two. Significant differences between observed and predicted HVs were observed in year one of rhGH therapy (p=<0.01), but not in year two (p=0.19) (n=11). 55% achieved HVs below the predicted range. There was no relationship between the observed and predicted HV discrepancy and the rhGH dose, suggesting that patient compliance may be a factor in the failure to attain predicted HVs. In year one, baseline pre-treatment insulin-like growth factor-1 (IGF-1) levels were negatively correlated to the difference between observed and predicted HV (figure 2 ). Conclusion: In children with IGHD receiving rhGH therapy: – Improvements in HV were observed, although considerable variability is seen particularly in year two. – Prediction models do not appear to give an accurate year one growth prediction. – Baseline IGF-1 level may be a valuable parameter for future growth prediction formulae. – Close attention to rhGH dose is needed in order to optimise growth responses.